2022
DOI: 10.1177/08258597221131133
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cancer-Related Fatigue among Cancer Patients: A Systematic Review

Abstract: Objectives: This systematic review aims to assess and explore various determinants of cancer- related fatigue. Methods: A systematic search of various determinants of Cancer-related fatigue (CRF) was performed in different databases like PubMed, Google Scholar, Science Direct and Clinical Key dating from 1990 to September 2020. Results: A total of 6115 studies were screened and 95 articles related to determinants of fatigue were retained. Various modifiable and non-modifiable determinants including socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Meanwhile, Chinese women are more tolerant and often hide their fatigue performance to avoid burdening their families, mistakenly believing that fatigue is only temporary. However, studies have shown[ 18 ] that persistent CRF leads to a higher risk of death. The findings of this research demonstrated that after the intervention, the observation group’s PFS-R scale scores on each dimension and overall were lower than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Chinese women are more tolerant and often hide their fatigue performance to avoid burdening their families, mistakenly believing that fatigue is only temporary. However, studies have shown[ 18 ] that persistent CRF leads to a higher risk of death. The findings of this research demonstrated that after the intervention, the observation group’s PFS-R scale scores on each dimension and overall were lower than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study severe fatigue was already present at baseline and significantly worsened over time. Many factors (modifiable and non-modifiable) have been identified to affect cancerrelated fatigue [21]. Particularly for patients with advanced cancer, earlier intervention (i.e., during systemic therapy) is needed and cognitive behavioral therapy or physical exercise programs during systemic therapy have shown to reduce the severity of cancer-related fatigue [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that several factors, including anemia, insomnia, anxiety, and depression, are essential for the occurrence and development of fatigue in patients with cancer (19)(20)(21).…”
Section: Risk Factorsmentioning
confidence: 99%